Navigating Diversity: The Emotional Toll and Educational Imperatives of Student Social Interaction in Multicultural Campuses - Hermanto; Trisyanti, Umi; Hidayah, Alfi Rohmatul (Journal of Communication in Scientific Inquiry (JCSI), 2025)
In multicultural and multilingual societies, understanding communication dynamics and their impacts is crucial. This study explores the management of communication and social interactions among university students within academic and social contexts. Through a questionnaire survey, the research analyses students’ experiences related to communication and social interaction on campus, including interactions with peers, lecturers, and administrative staff. The study focuses the experience of negative emotions s, such as feelings of anger, sadness, and disappointment and examines the strategies students employ to address these issues, both internally and externally. Additionally, the research investigates the role of social support from friends, family, and surrounding environment in overcoming communication problems. The study also evaluates the impact of negative emotions on students’ academic performance and social life and identifies the perceived needs for communication education and social interaction skills among students. Based on a survey of 126 students, the study finds that most respondents have experienced negative emotions the negatively affect their social and academic lives. The results also indicate that, although most students have received some form of communication training, there remains a need for more comprehensive communication education, particularly in verbal communication, public speaking, and communication ethics. These findings highlight the importance of developing a more effective communication curriculum to enhance the quality of social interactions on campus. Dalam masyarakat berbilang budaya dan bahasa, memahami dinamika komunikasi dan kesannya adalah penting. Kajian ini meneroka pengurusan komunikasi dan interaksi sosial dalam kalangan pelajar universiti dalam konteks akademik dan sosial. Melalui tinjauan soal selidik, kajian menganalisis pengalaman pelajar berkaitan komunikasi di kampus, termasuk interaksi dengan rakan sebaya, pensyarah, dan kakitangan pentadbiran. Fokus diberikan kepada pengalaman emosi negatif seperti marah, sedih, dan kecewa serta strategi dalaman dan luaran yang digunakan pelajar untuk mengatasinya. Kajian ini turut meneliti peranan sokongan sosial daripada rakan, keluarga dan persekitaran dalam menangani masalah komunikasi. Selain itu, kajian menilai kesan emosi negatif terhadap prestasi akademik dan kehidupan sosial pelajar serta keperluan terhadap pendidikan komunikasi dan kemahiran interaksi sosial. Berdasarkan data daripada 126 pelajar, didapati kebanyakan responden pernah mengalami emosi negatif yang memberi kesan terhadap kehidupan sosial dan akademik mereka. Walaupun majoriti pelajar pernah menerima latihan komunikasi, masih terdapat keperluan untuk pendidikan komunikasi yang lebih menyeluruh, khususnya dalam komunikasi lisan, pengucapan awam dan etika komunikasi. Dapatan ini menekankan kepentingan membangunkan kurikulum komunikasi yang lebih berkesan bagi meningkatkan kualiti interaksi sosial di kampus.